Domesticating Technology in Pandemic Social Work (Journal of Comparative Social Work, 2021)
On March 12th, 2020 the Norwegian government announced what later became known as ‘the lockdown’ of Norway due to the outbreak of Covid-19. This led to major changes in society where social distancing became the ‘new normal’ in everyday life. For social workers, it meant adapting to ‘new’ social problems among vulnerable groups as well as comprehensive changes in their working conditions and interactions with clients.Many social workers communicated with clients on digital platforms before the pandemic, but Norway’s Covid-19 social distancing policies changed the terms for using these platforms. This article investigates the impact of the pandemic on the ways Norwegian social workers involve themselves with digital technology in their interactions with clients. We employ domestication theory to investigate how social workers shape and navigate these new circumstances triggered by the pandemic using a three-dimensional model that includes practical, symbolic, and cognitive levels of analysis.The data underlying this article consist of 16 semi-structured interviews with social workers from seven different social services in Norway. The interviews were conducted approximately one month after the lockdown. The digital transformation within Norwegian social services, together with the changes related to the pandemic, have created new ways of practicing social work. We turn our attention to the following research questions: What characterized social workers’ digital interactions with clients during the first months of the pandemic? What can be learned from their experiences with domesticating technology? How has digital technology supported, challenged, and changed professional values in practice?